Photocatalytic decomposition of graphene over a ZnO surface under UV irradiation - Mun, Dae-Hwa; Lee, Hyun Jung; Bae, Sukang; Kim, Tea-Wook; Lee, Sang Hyun (ROYAL SOC CHEMISTRY, 2015)
Highly reactive radicals or chemicals are generated on the surfaces of oxide semiconductors via reactions between photo-induced charges and ambient gas molecules. These radicals or chemicals have been utilized in heterogeneous photosynthesis and photocatalysis. In this study, we demonstrated that the photocatalytic reactions on the surface of ZnO promoted the oxidation and decomposition of graphene. Raman spectra were used to analyze the evolution of the G and 2D peaks. The oxidation of graphene on a ZnO substrate by UV radiation was faster than that in the absence of ZnO. During oxidation, the resistivity and the transmittance of graphene also increased. The XPS results showed that functional groups related to the oxidation of graphene were formed during the photocatalytic reactions. This simple and clean approach will be also effective for selective surface modification by enhancing the surface chemical reactions that pattern graphene via oxidation.
Keywords: NITROGEN-DOPED GRAPHENE; TIO2